2017
DOI: 10.1007/s11408-017-0286-z
|View full text |Cite|
|
Sign up to set email alerts
|

Searching for a listed infrastructure asset class using mean–variance spanning

Abstract: This study examines the portfolio-diversification benefits of listed infrastructure stocks. We employ three different definitions of listed infrastructure and tests of mean-variance spanning. The evidence shows that viewing infrastructure as an asset class is misguided. We employ different schemes of infrastructure asset selection (both traditional asset classes and factor exposures) and discover that they do not provide portfolio-diversification benefits to existing asset allocation choices. We also find that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…The unlisted infrastructure assets are generally only available to institutional investors and such direct investment has many desired characteristics (Peng & Newell, 2007), (Finkenzeller et al, 2010), (Bitsch et al, 2010), (Blanc-Brude, 2013). The same is not with the listed infrastructure assets (Blanc-Brude et al, 2017), (Thierie & De Moor, 2016). Rather, the listed infrastructure assets resemble broad equities.…”
Section: Literature Reviewmentioning
confidence: 97%
“…The unlisted infrastructure assets are generally only available to institutional investors and such direct investment has many desired characteristics (Peng & Newell, 2007), (Finkenzeller et al, 2010), (Bitsch et al, 2010), (Blanc-Brude, 2013). The same is not with the listed infrastructure assets (Blanc-Brude et al, 2017), (Thierie & De Moor, 2016). Rather, the listed infrastructure assets resemble broad equities.…”
Section: Literature Reviewmentioning
confidence: 97%
“…The authors found that infrastructure acts more as a risk reducer than return enhancer in a multi-asset portfolio. In their seminal work, Blanc-Brude et al ( 2017 ) employ 22 proxies of infrastructure based on three different definitions identified from the literature in a comparative analysis using mean-variance spanning tests. The authors argue that infrastructure based on industry sector classification does not represent a separate asset class and is already spanned by existing capital market instruments.…”
Section: Reporting the Findingsmentioning
confidence: 99%
“…We find rather contradictory evidence on whether infrastructure exhibits risk-return profile that it promises or is simply a part of traditional investment vehicles on which it comes. While some studies (Peng and Newell 2007 ; Newell et al 2011 ; Oyedele et al 2013 ) present evidence of strong risk-adjusted performance and portfolio diversification potential of infrastructure and suggest a separate allocation in institutional investors’ portfolios, others (Bond et al 2007 ; Blanc-Brude et al 2017 ) contradict and argue that listed infrastructure cannot be considered a separate asset class and is rather a subset of general equity. For instance, Dechant and Finkenzeller ( 2012a , 2012b ) could not find evidence of infrastructure being a good hedge against long-term pension liabilities, thus, defying a long held notion.…”
Section: Reporting the Findingsmentioning
confidence: 99%
“…The study by Blanc-Brude et al (2017) examines portfolio diversification benefits of listed infrastructure stocks. It uses three different definitions of mean–variance spanning and for listed infrastructure.…”
Section: Literature Reviewmentioning
confidence: 99%